New Kids in Lactide Polymerization: Highly Active and Robust Iron Guanidine Complexes as Superior Catalysts. Issue 10 (19th March 2019) - Rittinghaus, Ruth D.; Schäfer, Pascal M.; Albrecht, Pascal; Conrads, Christian; Hoffmann, Alexander; Ksiazkiewicz, Agnieszka N.; Bienemann, Olga; Pich, Andrij; Herres‐Pawlis, Sonja
Abstract: Polylactide is a biodegradable versatile material based on annually renewable resources and thus CO2 ‐neutral in its lifecycle. Until now, tin(II)octanoate [Sn(Oct2 )] was used as catalyst for the industrial ring‐opening polymerization of lactide in spite of its cytotoxicity. On the way towards a sustainable catalyst, three iron(II) hybrid guanidine complexes were investigated concerning their molecular structure and applied to the ring‐opening polymerization of lactide. The complexes could polymerize unpurified technical‐grade rac ‐lactide as well as recrystallized l ‐lactide to long‐chain polylactide in bulk with monomer/initiator ratios of more than 5000:1 in a controlled manner following the coordination–insertion mechanism. For the first time, a biocompatible complex has surpassed Sn(Oct)2 in its polymerization activity under industrially relevant conditions. Abstract : Sn(Oct)2 beaten : Iron guanidine complexes exhibit extraordinarily high activity in lactide polymerization under industrially relevant conditions, polymerizing lactide in a controlled manner to long‐chain polymers. Thus, Sn(Oct)2 as traditional catalyst for the production of the bioplastic polylactide from annual renewables is finally beaten.